2015
DOI: 10.21236/ad1012700
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Enhanced in vivo Fitness of Neisseria gonorrhoeae Driven by a Fluoroquinolone Resistance-Conferring Mutant DNA Gyrase

Abstract: With no vaccine available, control of gonorrhea is seriously threatened by the evolution of heightened antibiotic resistance. The fluoroquinolone class of antibiotics served as a first-line treatment option for gonorrhea for only a limited period of time due to the proliferation of resistance mutations. Resistance to fluoroquinolones in Neisseria gonorrhoeae is achieved in a two-step process in which mutations in the quinolone resistance-determining regions of the genes encoding GyrA and ParC confer intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…mtrR mutations are likely to increase fitness due to overproduction of the MtrC-MtrD-MtrE efflux pump, which protects the gonococcus from innate antimicrobial effectors (25). The basis of the fitness advantage conferred by gyrA mutations (S91F/D95N) is unknown but may be a consequence of global changes in gene expression (27). In contrast to mtrR and gyrA mutations, PBP mutations that confer resistance to ␤-lactams are predicted to have a negative impact on gonococcal fitness based on fitness studies in Gram-positive organisms (28)(29)(30) and the importance of these enzymes in cell wall biosynthesis.…”
Section: Importancementioning
confidence: 99%
“…mtrR mutations are likely to increase fitness due to overproduction of the MtrC-MtrD-MtrE efflux pump, which protects the gonococcus from innate antimicrobial effectors (25). The basis of the fitness advantage conferred by gyrA mutations (S91F/D95N) is unknown but may be a consequence of global changes in gene expression (27). In contrast to mtrR and gyrA mutations, PBP mutations that confer resistance to ␤-lactams are predicted to have a negative impact on gonococcal fitness based on fitness studies in Gram-positive organisms (28)(29)(30) and the importance of these enzymes in cell wall biosynthesis.…”
Section: Importancementioning
confidence: 99%
“…Thus, multiple research groups have focused on the study of these fitness costs. D'Ambrozio et al found that a specific mutation in gyrA conferred a fitness advantage in vivo because of its effects on genome regulation [61,66]. These findings are supported by the fact that fluoroquinolone-resistant NG strains remain prevalent even after fluoroquinolones were discarded as primary treatment options.…”
Section: Mechanisms Of Resistance: Spreading and Fitnessmentioning
confidence: 97%